The Evolving Landscape of the Colorectal Cancer Vaccines: From Biological Mechanisms to Translational Therapeutics - Setiono, Sabrina Brigitta Valerie; Turalaki, Grace Lendawati Amelia; Tallei, Trina Ekawati (Heca Sentra Analitika, 2026)
Colorectal cancer (CRC) remains a major global health burden, and despite substantial advances in cancer immunotherapy, the clinical efficacy of therapeutic cancer vaccines in CRC has been limited. This review critically examines the biological, immunological, and translational factors that shape CRC vaccine development, with a particular focus on tumor immunopathology, antigen selection, vaccine platforms, and emerging combination strategies. We summarize current knowledge on CRC-associated tumor antigens, including selected tumor-associated antigens and neoantigen-based approaches, alongside major vaccine modalities evaluated in preclinical and early-phase clinical studies. Across the literature, vaccine-induced immunogenicity frequently exceeds demonstrated clinical benefit, highlighting a persistent translational gap. Synthesis of available evidence suggests that this gap is driven primarily by CRC-specific immune constraints, including immune exclusion, dominance of immunologically cold MSS/pMMR tumors, and tolerogenic pressures within metastatic niches, particularly the liver. We further discuss how rational combination strategies, especially those integrating cancer vaccines with immune checkpoint inhibitors (ICIs), may partially overcome these barriers. In addition, the review outlines the conceptual role of bioinformatics and immunoinformatics in supporting antigen prioritization, neoantigen discovery, and patient stratification in CRC vaccine research. Overall, this review emphasizes that future progress will depend on CRC-tailored antigen selection, mechanistically informed vaccine design, rational combination regimens, and rigorous clinical evaluation to define the realistic clinical role of therapeutic cancer vaccines in CRC.